(3QMjb GdCfgGQ aj QLGd GdCRgGQs - (3CMeO Hf YHO Gddg Hf YHO GdQMef GdLfOGQj, GdLfOGQjs ((3eMeO Hf ESeGYjd Hf jMji Hf GdMSjf s)
(3ChdgG (B:s
(3gPg fHPg ai QLGd TQM GdCRgGQ GdeSei HGdefJRY hGdeNJGQ ef GdZjK GdeOQGQ , QJQJgG Ydi MQha GdeYLe hGdZQV GdGNJUGQ h JHjjf GSe GdQLd heG ZHQJ Ydjg ef CMhGdg hehdOg Ch haGJg s
(3BNQgG (B:s
(3MQa GdjGA (B: (3jhSa Hf jMji GdHhjWi cGf YGHOkG hde jRd eSLhfkG MJi Jhai HHZOGO SfI EMOi hKdGKjf heGFJjf hgPG BNQ eG JjSQ EdMGbg HGdCUd GfJgi s
(3GdfSNI HgG MhGTs
(3HgG GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ ahGJMgG HGdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdJGQjNs